Prevalence of Duodenal Diverticulum in South Indians: A Cadaveric Study. (7th November 2013) - Sakthivel, Sulochana; Kannaiyan, Kavitha; Thiagarajan, Sivakami
Abstract : Background . Duodenum is the second most common site of diverticula after the colon. Diagnosis of duodenal diverticula is incidental and found during other therapeutic procedures. In 90% of cases, they are asymptomatic, and less than 10% develop clinical symptoms. The difficulty to ascertain the true incidence of duodenal diverticula demanded for the present study to elucidate the prevalence of the duodenal diverticulum in South Indians. Materials and Methods . One hundred and twenty specimens of duodenum were utilized for the study. The prevalence, anatomical location, and dimension of duodenal diverticulum were studied. Results . Among the 120 specimens of duodenum, five specimens had solitary, extraluminal, and globular-shaped diverticula in the medial wall of the duodenum. In three (60%) cases, it was found in the second part of duodenum and in two (40%) cases in the third part. The mean size of the diverticula was 1.4 cm. Conclusion . In the present study in South Indian people, the prevalence (4.2%) of duodenal diverticula is low comparable to other studies in the literature. Even though most of the duodenal diverticula are asymptomatic, the knowledge about its frequency and location is of great importance to prevent complications like diverticulitis, hemorrhage, obstructive jaundice, and perforation.